APPROACHES TO THE CONCEPTS OF PRODUCTIVITY, EFFICIENCY AND EFFECTIVENESS IN THE FIELD OF SCIENTIFIC RESEARCH AND DEVELOPMENT - O. F. Seliverstova (Фармакоэкономика)
The article analyzes the Russian and foreign approaches to the disclosure of the terms "effectiveness", "productivity", "efficiency". Identified, analyzed concepts are closely related, however, there is currently no generally accepted formulations, which can lead to misunderstandings, errors in managerial decision-making needs to be redressed. Recommendations on fixing these concepts in normative legal and methodical documents regulating, in particular the development of science, and establishing indicators of results, efficiency and effectiveness of research organizations.